Long-Term Adiposity and Midlife Carotid Intima-Media Thickness Are Linked Partly Through Intermediate Risk Factors. Issue 1 (31st October 2022) - Zhang, Tao; Fan, Bingbing; Li, Shengxu; Wang, Xuan; Kong, Yawei; Bazzano, Lydia; He, Jiang; Chen, Wei; Yan, Yinkun
Abstract : Objective: This study aims to determine quantitatively the mediation effects of multiple cardiovascular risk factors on the associations of childhood body mass index (BMI) and its cumulative burden with adult carotid intima-media thickness (cIMT). Methods: The longitudinal cohort consisted of 1391 adults who had been examined for BMI 4-15 times over 35.0 years on average since childhood and had data on adult cIMT, systolic blood pressure, low-density lipoprotein cholesterol, atherogenic index of plasma, and serum glucose. The area under the curve was used as a measure of cumulative burden of BMI. Results: After adjusting for covariates, the total effects (standardized regression coefficient) of childhood BMI (0.138), adult BMI (0.111), and area under the curve of BMI (0.150) on cIMT were all significant ( P <0.001) without mediators included in the model. The mediation effects of adult systolic blood pressure, glucose, atherogenic index of plasma and low-density lipoprotein cholesterol were 8.0%, 4.3%, 3.6%, and 0.0%, respectively, in the model with childhood BMI as the predictor, 23.4%, 15.3%, 12.6%, and 7.2%, respectively, with adult BMI as the predictor, and 14.7%, 8.7%, 6.0%, and 2.0%, respectively, with area under the curve of BMI as the predictor. The direct effects on cIMT were 0.117 ( P <0.001) for childhood BMI, 0.046 ( P =0.224) for adult BMI, and 0.103 ( P <0.001) for area under the curve of BMI after removing the mediation effects. Conclusions: The long-term deleterious impact of adiposity on subclinical changes in vascular structure begins early in life and is accumulated over lifetime. Excess adiposity and higher cIMT are linked partly through other cardiovascular risk factors in later life, especially elevated blood pressure and glucose.